Spectral properties of retro-reflective materials from experimental measurements - Shuhan Liu; Jing Wang; Xi Meng (Case Studies in Thermal Engineering, 2022)
Retro-reflective (RR) materials have received much attention due to their retro-reflective optical properties, which has essential differences with the diffuse reflection of traditional highly-reflective materials. As a guide to determine the performance improvement and the building applications of RR materials, the spectral characteristics are measured and related to the typical glass-bead and prism RR materials. The integrating sphere is used to measure the global reflectivity of the two RR materials, while a new instrument is developed to study the angular distribution and the retro-reflectivity of two RR materials at different incident angles. The results show that the global reflectivity is found to be 68.08% and 51.44% for the glass-bead and Prism RR materials, respectively, but the retro-reflectivity of the prism RR material is 12.56% higher than that for the glass-bead RR materials. The RR materials display the greatest different for the retro-reflectivity under the different radiation wavelengths. The variation trend of the retro-reflectivity is distinct for different wavelength ranges: the higher the wavelength, the lower the retro-reflectivity. Increasing the incident angle could reduce the retro-reflective property of the RR materials, and the incident angle had a high impact on radiation wavelengths less than 1200 nm. With the incident angle increased from 0° to 80°, the retro-reflectivity is reduced by 40.58–48.60% for the 800 nm wavelength, 35.40–45.13% for the 900 nm, 23.43–26.01% for 1000–1200 nm, and 8.64–13.71% for 1300–1600 nm.